Responses of microbial community and soil enzyme to heavy metal passivators in cadmium contaminated paddy soils: An in situ field experiment. (October 2021) - Jiang, Yuexi; Hu, Ting; Peng, Ou; Chen, Anwei; Tie, Baiqing; Shao, Jihai
Abstract: Heavy metal passivators could reduce the transfer of heavy metal ions from soil to crops and exhibit great potential in safe cropping in heavy metal contaminated agricultural soils. However, the effects of heavy metal passivators on microbial diversity and microorganisms-based biogeochemical processes in agricultural soil are poorly explored. In this study, the effects of three heavy metal passivators, viz. lime, silicon (Si) fertilizer, and gypsum, on the structure and function of microorganisms in cadmium (Cd) contaminated paddy soils were investigated through activity of soil enzyme, microbial abundance and community structure by an in situ paddy field plot experiment. Our results showed that lime application changed the activity of phosphatase and urease through increasing bio-available phosphorus (AP) content in soil and soil pH, respectively. Lime application increased abundance and richness of the prokaryotic microbes in paddy soil, while gypsum application increased evenness of the eukaryotic microbes. Si fertilizer application resulted in the increase of evenness of both prokaryotic and eukaryotic microbes. The results presented in this study suggest that application of heavy metal passivator lime, Si fertilizer, and gypsum could improve microbial diversity and function in Cd contaminated paddy soil. Graphical abstract: Image 1 Highlights: Lime application reduced activity of phosphatase but increased activity of urease. Lime application increased population density and richness of prokaryotic microbes. Si application increased evenness of both prokaryotic and eukaryotic microbes. Gypsum application increased evenness of eukaryotic microbes. Variations of pH, AP, ASi, and ACI-Cd affected the structure of microbial community.